Peoples and Crafts in Period IVB at Hasanlu, Iran - Schauensee, Maude de (Book collections on Project MUSE., 2011)
The University of Pennsylvania Museum of Archaeology and Anthropology has had a long-standing interest in the archaeology of Iran. In 1956, Robert H. Dyson, Jr., began excavations south of Lake Urmia at the large mounded site of Hasanlu. Although the results of these excavations await final publication, the Hasanlu Special Studies series-of which this monograph is the fourth volume-describes and analyzes specific aspects of technology, style, and iconography. This volume describes a group of ongoing research projects, most of which provide new information on Iron Age technology. A theme that runs through these studies is the degree to which ancient workers varied the composition of their products to create desirable colors and textures.The book begins with a description of the wooden furniture fragments along with fittings and decorative elements for furniture. It presents the first detailed description of the charred textiles, and places these textiles in their archaeological contexts, suggesting the roles that textiles may have played in daily life. Later chapters assess the significance of Hasanlu in the history of glassmaking, describe the archaeometallurgy of the Hasanlu IVB bronzes, and present a catalog of the bladed weapons. Also, the book presents the evidence for deliberate violence against individuals as indicated by their skeletal injuries and the results of a project undertaken to determine whether DNA could be used to obtain a better understanding of the population history at Hasanlu.Content of the book's DVD-ROM may be found online at this location: http://core.tdar.org/project/375174.University Museum Monograph, 132.